2002
DOI: 10.1093/emboj/cdf300
|View full text |Cite
|
Sign up to set email alerts
|

Control of germination and lipid mobilization by COMATOSE, the Arabidopsis homologue of human ALDP

Abstract: S.Footitt, S.P.Slocombe and V.Larner contributed equally to this workEmbryo dormancy in¯owering plants is an important dispersal mechanism that promotes survival of the seed through time. The subsequent transition to germination is a critical control point regulating initiation of vegetative growth. Here we show that the Arabidopsis COMATOSE (CTS) locus is required for this transition, and acts, at least in part, by profoundly affecting the metabolism of stored lipids. CTS encodes a peroxisomal protein of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
301
2
23

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(351 citation statements)
references
References 60 publications
23
301
2
23
Order By: Relevance
“…The same is true for worms and insectae; only one ABCD halfway between ABCD1 and ABCD2 can be found in their genomes. Plants, here represented by Oryza sativa and Arabidopsis thaliana, do not have any ABCD1-ABCD2 homologue; their closest ABCD, the comatose protein, is more similar to ABCD3 than to ABCD1 in contrast to previous reports (13). Fungi have two ABCD related proteins: Pxa2p and Pxa1p, which appear closer to ABCD1-2 than to ABCD3 or ABCD4, although they are more similar to one another than to any metazoan ABCD ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The same is true for worms and insectae; only one ABCD halfway between ABCD1 and ABCD2 can be found in their genomes. Plants, here represented by Oryza sativa and Arabidopsis thaliana, do not have any ABCD1-ABCD2 homologue; their closest ABCD, the comatose protein, is more similar to ABCD3 than to ABCD1 in contrast to previous reports (13). Fungi have two ABCD related proteins: Pxa2p and Pxa1p, which appear closer to ABCD1-2 than to ABCD3 or ABCD4, although they are more similar to one another than to any metazoan ABCD ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…35 In A. thaliana, 3 independent experimental approaches have identified the same peroxisomal transporter, named CTS /PXA1/PED3, as responsible for the translocation of at least part of the fatty acids for b-oxidation. 31,38,39 It has been suggested that CTS /PXA1/PED3 might not be the only transporter for b-oxidation substrates into the peroxisome 34 and a LTP may be reasonable implicated in this process. A mayor concern to consider this hypothesis is the subcellular location of LTP3.…”
Section: Resultsmentioning
confidence: 99%
“…Following mechanical rupture of the testa and seedling establishment in the presence of exogenous Suc, cts mutants can be transferred to soil and complete the life cycle (Russell et al, 2000;Footitt et al, 2002). However, mutation of CTS had subtle effects on vegetative growth: Rosette leaf number and area were reduced in cts-1 mutants compared to the wild type, Landsberg erecta (Ler), but these parameters were much less affected in cts-2 mutants, which more closely resembled the wild type, Wassilewskija2 (Ws2; Supplemental Fig.…”
Section: Postgerminative Phenotype Of Cts Mutantsmentioning
confidence: 99%
“…Isolation of cts-1 and cts-2 has been described previously (Footitt et al, 2002). Seeds of kat2-1 and lacs6-1,lacs7-1 were the kind gifts of Professor Steve Smith (University of Western Australia) and Dr. Martin Fulda (University of Gö ttingen), respectively.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation